KONSEP SABAR DAN IKHLAS MENGHADAPI MUSIBAH DALAM HADIS DAN APLIKASINYA DI KECAMATAN SIMANGAMBAT KABUPATEN PADANG LAWAS UTARA - Abdul Halim; Munandar Munandar; Siti Asna Harahap (UIN Sumatera Utara Medan, 2022)
As a believer, we are never separated from tests and trials, because this is proof of Allah SWT's love for His servants, these trials and tests can turn into misfortune or pleasure. Every disaster that occurs on this earth is a decree from Allah SWT. So we must accept it sincerely and be patient with its provisions, and believe and believe that every disaster that occurs is destiny from Allah SWT. And the reward for those who are patient is when we are hit by a disaster, be it a small disaster or a big disaster. And Allah always tells us to be sincere, because sincerity is the highest practice than patience. And the calamity that Allah SWT has given us is as an eraser for our sins (mistakes) and Allah SWT will elevate the degrees of those who are afflicted with calamities